X‐ray structures of Nfs2, the plastidial cysteine desulfurase from Arabidopsis thaliana. Issue 9 (1st September 2014) - Roret, Thomas; Pégeot, Henri; Couturier, Jérémy; Mulliert, Guillermo; Rouhier, Nicolas; Didierjean, Claude
Abstract : The chloroplastic Arabidopsis thaliana Nfs2 (AtNfs2) is a group II pyridoxal 5′‐phosphate‐dependent cysteine desulfurase that is involved in the initial steps of iron–sulfur cluster biogenesis. The group II cysteine desulfurases require the presence of sulfurtransferases such as SufE proteins for optimal activity. Compared with group I cysteine desulfurases, proteins of this group contains a smaller extended lobe harbouring the catalytic cysteine and have a β‐hairpin constraining the active site. Here, two crystal structures of AtNfs2 are reported: a wild‐type form with the catalytic cysteine in a persulfide‐intermediate state and a C384S variant mimicking the resting state of the enzyme. In both structures the well conserved Lys241 covalently binds pyridoxal 5′‐phosphate, forming an internal aldimine. Based on available homologous bacterial complexes, a model of a complex between AtNfs2 and the SufE domain of its biological partner AtSufE1 is proposed, revealing the nature of the binding sites.